Antipsychotics Prevent Psychosine Induced Toxicity in Glial Cells. - Sharma, Kapil (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2023)
Glial cells are implicated in the neuropathophysiology of schizophrenia and other neuropsychiatric disorders. Also, the role of altered myelin in the onset and development of schizophrenia and changes in myelin due to antipsychotics remains unclear. There is growing interest in the effects of antipsychotics on glial cells, to explore the ways these drugs may act via non-neuronal mechanisms. To investigate if antipsychotic drugs modulate glial cell dysfunction, human astrocytes were treated with the toxin psychosine, with or without antipsychotics (chapter 3). MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) and LDH (Lactate Dehydrogenase) assays showed that psychosine decreased cell viability and induced cell toxicity in human astrocytes. This was returned to almost control levels by antipsychotics. Immunocytochemical analysis showed that psychosine impaired astrocyte morphology which was reversed significantly by antipsychotics. Selective D2 and 5HT2A receptor antagonists were found to attenuate psychosine-induced decrease in cell viability, toxic effects, and reductions in astrocyte processes with advantage of dopamine over serotonin antagonism (Results, chapter 3). The effects of the antipsychotics, haloperidol and clozapine, on levels of myelin using mouse organotypic cerebellar slices treated with the demyelinating agent psychosine was also investigated (Chapter 4). Psychosine induced a concentration-dependent loss of myelin. Importantly, both haloperidol and clozapine, reduced this psychosine-induced loss. Similarly, these drugs attenuated psychosine-induced loss of astrocyte markers. Psychosine also induced a decrease in nonphosphorylated neurofilament levels, which were restored by both haloperidol and clozapine, indicating neuroprotective and neurorestorative processes (Results, chapter 4). Having shown that antipsychotics prevented psychosine toxicity to human astrocytes in-vitro and ameliorated psychosine induced demyelination in mouse organotypic cerebellar slice cultures ex-vivo. Another study aimed to examine if these findings would translate into improved survival, mobility, and behavioural metrics in an in-vivo model of psychosine toxicity i.e., the twitcher mouse model of Krabbe Disease (Chapter 5). The antipsychotic haloperidol increased survival, improved mobility, and positively influenced behaviours in twitcher mice (Results, chapter 5). Overall, this work suggests that antipsychotics may regulate astrocyte cell damage and exert a protective effect on oligodendrocytes. Also, this suggests that antipsychotics or agents with similar pharmacology, namely D2/5HT2A receptor antagonists, may be a potential novel treatment for KD, a leukodystrophy that leads to the accumulation of the toxin psychosine.
APPROVED
Keywords: Haloperidol; Astrocytes; Antipsychotics; Twitcher mice; Psychosine; Krabbe disease; Schizophrenia; Demyelination